2022
DOI: 10.1002/sstr.202100219
|View full text |Cite
|
Sign up to set email alerts
|

Toward Eco‐Friendly Lead‐Free Low‐Dimensional Perovskites

Abstract: Lead halide perovskites are regarded as potential successor of traditional perovskites, due to their variable structures and excellent optoelectronic properties. However, its large‐scale commercialization is impeded by the inherent instability and toxicity. In this regard, lead‐free low‐dimensional perovskites (LFLDPs) have emerged as promising alternatives to the traditional 3D components, due to their structural tunability and environmental friendliness and stability. The structure–property characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 123 publications
(163 reference statements)
0
8
0
Order By: Relevance
“…Recently, lead-free layered perovskites have emerged as promising alternatives to conventional lead-based 3D components due to its environmental friendliness and structural tunability. [45][46][47] Though the PCE of 2D perovskites in solar cells is yet to be enhanced in order to contest with the 3D counterpart due to the restricted carrier transport, layered perovskites can play a multi-functional role inside a solar cell, such as a passivating layer, capping layer, active absorber, etc. [48][49][50][51] Interestingly, multidimensional 2D-3D perovskites-based solar cells exhibit long-term stability and high performance simultaneously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, lead-free layered perovskites have emerged as promising alternatives to conventional lead-based 3D components due to its environmental friendliness and structural tunability. [45][46][47] Though the PCE of 2D perovskites in solar cells is yet to be enhanced in order to contest with the 3D counterpart due to the restricted carrier transport, layered perovskites can play a multi-functional role inside a solar cell, such as a passivating layer, capping layer, active absorber, etc. [48][49][50][51] Interestingly, multidimensional 2D-3D perovskites-based solar cells exhibit long-term stability and high performance simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, lead‐free layered perovskites have emerged as promising alternatives to conventional lead‐based 3D components due to its environmental friendliness and structural tunability. [ 45–47 ]…”
Section: Introductionmentioning
confidence: 99%
“…As Ge‐based perovskites, photovoltaic cells are numerically modelled to match better with the energy band of the selected charge transporting layer 55 . Numerous theoretically investigated lead‐free low‐dimensional perovskites are found to have unique structure‐property characteristics, which endow them with a combination of optoelectronic efficiency and versatile functionality, offering state‐of‐the‐art employment in the optoelectronic devices 56 …”
Section: Introductionmentioning
confidence: 99%
“…55 Numerous theoretically investigated lead-free low-dimensional perovskites are found to have unique structure-property characteristics, which endow them with a combination of optoelectronic efficiency and versatile functionality, offering state-of-the-art employment in the optoelectronic devices. 56 For n = 1, the monolayer perovskites with the structure of (R-NH 3 ) 2 BX 4 consist of a single sheet of octahedral cages being sandwiched between the non-polar spacers thus shielding the chemically active sites from externally invasive polar water molecules. 57 Furthermore, ultrathin sheets offer a quantum dot-like configuration, which provides excellent quantum and dielectric confinement to produce stable exciton for highly efficient solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) lead halide perovskites with a large optical absorption coefficient, tunable bandgap, and facile solution fabrication processing have been considered as promising energy-conversion materials in photovoltaic and light-emitting diode (LED) applications. , However, the inherent instability and toxicity hinder their future commercial development . Recent studies on low-dimensional lead-free halide perovskites demonstrated their high photoluminescence quantum yield (PLQY) and excellent stability, which benefit high-performance LEDs. Wang et al demonstrated 2D perovskite LEDs based on 7-(thiophen-2-yl)­benzothiadiazol-4-yl)-[2,2′-bithiophen]-5-yl)­ethylammonium tin iodide (BTm) 2 SnI 4 , which exhibited a reasonably good PLQY of 7.8% and an operational stability of over 150 h . Creason et al reported the blue-emitting 1D perovskite Rb 2 CuBr 3 with a high PLQY of 64%, which showed no significant weight loss up to 475 °C .…”
mentioning
confidence: 99%